Rapid evaluation method of fly ash or cement volume stability

CN122882518APending Publication Date: 2026-10-09XINJIANG AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610997715.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明目的在于针对现有技术中无法快速检测粉煤灰中f-CaO活性的问题,提供一种粉煤灰或水泥体积安定性的快速评价方法,通过建立f-CaO含量、基准电导率的关系,快速确定待测样品中f-CaO的活性,并通过建立f-CaO活性、f-CaO含量与安定性的等值线图,快速判断待测样品的体积安定性,能够满足工程快速验收粉煤灰的需求

Benefits of technology

[0043]由以上本发明的技术方案可见,本发明提出的粉煤灰或水泥体积安定性的快速评价方法,通过测定粉煤灰或者水泥中f-CaO在乙二醇的电导率,再同特定温度条件下煅烧获得等质量f-CaO的电导率进行对比,可快速确定粉煤灰和水泥中f-CaO的活性,从而能更准确快速地判断粉煤灰和水泥中f-CaO对安定性的影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122882518A_ABST
    Figure CN122882518A_ABST
Patent Text Reader

Abstract

The application discloses a method for rapidly and quantitatively detecting f-CaO activity in fly ash or cement, and rapidly evaluates the volume stability of fly ash based on the method, establishes a reference conductivity by using f-CaO standard samples selected in a specific manner, obtains an activity index L for quantitatively representing the reaction activity of f-CaO by calculating the ratio of an actual conductivity to the reference conductivity, and predicts the Lea's clamp expansion value by combining the activity index L and the actual mass fraction P of f-CaO in the sample to be detected with a pre-established stability contour map of fly ash or cement, so that the stability determination is rapidly completed. The application establishes the activity index L of f-CaO as a quantitative evaluation parameter of activity, and establishes a volume stability evaluation system taking the actual mass fraction P and the activity index L of f-CaO as two-dimensional evaluation parameters and taking the Lea's clamp expansion value as an evaluation target, so that the rapid evaluation of the volume stability of fly ash or cement is realized, and the engineering rapid acceptance requirement can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fly ash or cement testing technology, and more specifically to a rapid detection method for f-CaO activity in fly ash or cement and a rapid test method for the volume stability of fly ash or cement. Background Technology

[0002] Fly ash is a solid waste emitted from coal-fired power plants and is widely used as a concrete admixture. Free calcium oxide (f-CaO) is a key factor affecting the stability of fly ash. The main reason for the poor stability of f-CaO is that some f-CaO is coated with a dense glassy phase or forms dense, dead-burned CaO, which reduces its hydration activity and makes its reaction with water extremely slow. After the cement paste hardens, this delayed-hydration f-CaO continues to react to form Ca(OH)2, causing volume expansion and thus poor stability.

[0003] The national standard "Fly Ash for Cement and Concrete" (GB / T 1596-2017) specifies the limit requirements for f-CaO content. However, engineering practice shows that even if the f-CaO content meets the national standard, poor stability may still occur. This is because the activity of f-CaO varies: highly active f-CaO has a loose structure and can react in the early stages of cement hydration, releasing its expansion early and having little impact on stability; while low-activity f-CaO, due to its dense structure or surface glassy coating, undergoes delayed hydration, reacting slowly only after the cement has hardened, resulting in late-stage expansion and poor stability.

[0004] Currently, there is a lack of effective evaluation methods for the f-CaO activity during fly ash acceptance testing. Traditional stability testing uses the Le Chatelier clamp method, which requires samples to be cured for 24 hours or even longer, failing to meet the needs of rapid project acceptance. Existing conductivity methods (such as the rapid detection device for free calcium oxide in fly ash disclosed in CN221803886U) can quickly determine the f-CaO content, but they only reflect the "quantity" and cannot distinguish the "activity," that is, they cannot determine the rate of f-CaO hydration reaction and its potential impact on stability.

[0005] Therefore, while ensuring that the f-CaO content meets the national standard, it is also necessary to quickly and quantitatively evaluate the activity of f-CaO in order to more accurately determine the volume stability of fly ash. Summary of the Invention

[0006] The purpose of this invention is to address the problem of the inability to quickly detect the f-CaO activity in fly ash in existing technologies, and to provide a rapid evaluation method for the volume stability of fly ash or cement. By establishing the relationship between f-CaO content and reference conductivity, the activity of f-CaO in the sample to be tested can be quickly determined. Furthermore, by establishing contour maps of f-CaO activity, f-CaO content, and stability, the volume stability of the sample to be tested can be quickly determined, which can meet the needs of rapid acceptance of fly ash in engineering projects.

[0007] According to a first aspect of the present invention, a rapid quantitative detection method for f-CaO activity in fly ash or cement is provided, characterized by comprising the following steps:

[0008] S1-1. Prepare highly active f-CaO standard samples and establish an activity benchmark.

[0009] Analytical pure calcium carbonate was calcined to constant weight at multiple gradient temperature points in the range of 950℃ to 1350℃ to obtain a series of calcined products.

[0010] The f-CaO content in each calcined product was determined, and calcined products in which the difference between the measured value and the theoretical weighing value was within ±5% of the theoretical weighing value were identified as candidate f-CaO samples.

[0011] Each candidate f-CaO sample was incorporated into fly ash or cement matrix without f-CaO at the same mass fraction and homogenized, and then subjected to Le Chatelier stability test.

[0012] Among the candidate samples with a Rabcat expansion value of no more than 5.0 mm, the sample with the lowest corresponding calcination temperature was selected as the f-CaO standard sample, and the activity index was defined as 100% as the benchmark.

[0013] S1-2. Establish a quantitative relationship between f-CaO content and reference conductivity.

[0014] Different mass fractions of the f-CaO standard samples were added to several equal masses of fly ash or cement matrix containing no f-CaO, to obtain a series of standard samples with an f-CaO mass fraction of 0.5% to 10.0%.

[0015] Each standard sample was added to a mixed solution of ethylene glycol and anhydrous ethanol in a volume ratio of 2:1, and extracted by standing at room temperature for 10 min to 30 min until the f-CaO extraction reached a stable state. The conductivity of each extract was measured, and a quantitative relationship curve between f-CaO content and reference conductivity was established.

[0016] S1-3. Determine the actual conductivity of the sample to be tested.

[0017] Weigh the sample to be tested with the same mass as the standard sample, add it to a mixed solution of ethylene glycol and anhydrous ethanol in a volume ratio of 2:1, and extract it by standing for 10 min to 30 min under the same room temperature conditions until the f-CaO extraction reaches a stable state. Measure the actual conductivity σ' of the extract.

[0018] S1-4, Calculate the activity index

[0019] The actual mass fraction P of f-CaO in the sample to be tested is determined, and the reference conductivity σ0 corresponding to the actual mass fraction P is obtained according to the quantitative relationship curve described in step S1-2; the activity index L of f-CaO in the sample to be tested is calculated according to formula (1):

[0020] (1)

[0021] In the formula: L is the activity index; σ' is the actual conductivity, in μs / cm; σ0 is the reference conductivity, in μs / cm;

[0022] S1-5. Determine the f-CaO activity in the sample to be tested.

[0023] The activity level of f-CaO in the sample to be tested is determined based on the activity index L calculated in steps S1-4.

[0024] When L=100%, the activity of f-CaO in the test sample is determined to be equivalent to that of the f-CaO standard sample.

[0025] When L < 100%, the activity of f-CaO in the test sample is determined to be lower than that of the f-CaO standard sample;

[0026] When L > 100%, the activity of f-CaO in the test sample is determined to be higher than that of the f-CaO standard sample;

[0027] The entire testing process was completed within 30 minutes.

[0028] As an optional implementation, the gradient temperature in step S1-1 is a temperature point with an interval of 50°C, including: 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C and 1350°C.

[0029] As an optional implementation, the conductivity measurement process in steps S1-2 and S1-3 includes: taking two consecutive measurements using a calibrated conductivity meter, and using the average of the two measurements as the conductivity value; wherein the relative error of the two parallel tests is not greater than 10%, and if the relative error is greater than 10%, the measurement is repeated.

[0030] According to a second aspect of the present invention, a rapid test method for the volume stability of fly ash or cement is provided. This method utilizes the aforementioned method to determine the activity index L and actual mass fraction P of f-CaO in the sample to be tested, and combines this with a pre-established fly ash or cement stability contour map to predict the Reichstag expansion value, completing the stability determination within 30 minutes. The method includes the following steps:

[0031] S2-1. Preparation of industrial f-CaO samples

[0032] Industrial limestone was calcined at 1350℃ to constant weight to obtain industrial f-CaO samples;

[0033] S2-2. Prepare a series of fly ash or cement samples and determine their soundness parameters.

[0034] Different mass fractions of the industrial f-CaO samples were added to several equal masses of fly ash or cement matrices that did not contain f-CaO to obtain a series of fly ash or cement samples.

[0035] The actual mass fraction and activity index of f-CaO in each fly ash or cement sample were determined using the aforementioned method. At the same time, the Le Chatelier stability test was performed and the Le Chatelier expansion value of each fly ash or cement sample was determined.

[0036] S2-3. Establish contour maps of fly ash or cement stability.

[0037] Using the actual mass fraction of f-CaO as variable X, the activity index of f-CaO as variable Y, and the expansion value of the Le Chatelier as variable Z, the data were fitted using the projection pursuit regression (PPR) model, and contour maps of the stability of fly ash or cement were drawn.

[0038] S2-4. Rapidly determine the stability of the sample to be tested.

[0039] The actual mass fraction P and activity index L of f-CaO in the sample to be tested are determined, and the predicted values ​​of the Le Chatelier expansion corresponding to P and L are retrieved from the stability contour map of fly ash or cement.

[0040] When the predicted expansion value of the Le Chatelier clip is not greater than 5.0 mm, the volume stability of the sample to be tested is deemed to be qualified.

[0041] As an optional implementation, the process of drawing the fly ash or cement stability contour map in step S2-3 includes: using no less than 20 sets of measured data as sample data sources to perform the PPR modeling and fitting, and drawing contour maps based on the modeling results, wherein the expansion value interval between adjacent contour lines in the contour map is 0.5 mm.

[0042] As an optional implementation, the process of retrieving the predicted values ​​of the Le Chatelier expansion corresponding to P and L from the fly ash or cement stability contour map includes: obtaining the predicted values ​​of the Le Chatelier expansion corresponding to P and L through linear interpolation or model calculation based on the fly ash or cement stability contour map.

[0043] As can be seen from the above technical solutions of the present invention, the rapid evaluation method for the volume stability of fly ash or cement proposed in this invention can quickly determine the activity of f-CaO in fly ash and cement by measuring the conductivity of f-CaO in ethylene glycol in fly ash or cement and comparing it with the conductivity of an equal mass of f-CaO obtained by calcination under specific temperature conditions. This allows for a more accurate and rapid assessment of the impact of f-CaO in fly ash and cement on stability.

[0044] The rapid evaluation method for the volume stability of fly ash or cement of the present invention can be controlled within 30 minutes, which can meet the needs of rapid acceptance of fly ash in engineering projects. Moreover, the method is convenient, effective, easy to master, and meets the requirements for industrial promotion. Attached Figure Description

[0045] Figure 1 This is a fitted curve showing the relationship between f-CaO content and theoretical active conductivity in an example of this invention.

[0046] Figure 2 This is a contour map showing the relationship between f-CaO content, f-CaO activity, and volume stability in fly ash. Detailed Implementation

[0047] To better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.

[0048] Various aspects of the invention are described in this disclosure with reference to the accompanying drawings, in which numerous illustrative embodiments are shown. The embodiments of this disclosure are not necessarily intended to encompass all aspects of the invention. It should be understood that the various concepts and embodiments described above, as well as those described below in more detail, can be implemented in any of a number of ways.

[0049] This invention constructs a method for rapidly and accurately evaluating the volume stability of fly ash or cement, accurately and quickly determining the activity of f-CaO, and clarifying its impact on stability in combination with the f-CaO content in fly ash or cement, thereby improving the efficiency of fly ash acceptance in engineering projects.

[0050] In designing the method for determining f-CaO activity, this invention adhered to the following conditions:

[0051] (1) The reaction solvent or extractant should not react with more reactive metal oxides such as Na2O and K2O;

[0052] (2) Do not add acids, bases, or other substances that readily react with Na2O and K2O to perform colorimetric reactions for identification;

[0053] (3) It is not advisable to carry out the activity in a high-temperature environment;

[0054] (4) React as quickly as possible and make judgments as short as possible.

[0055] Rapid quantitative detection method for f-CaO activity in fly ash or cement

[0056] The present invention provides an exemplary rapid quantitative detection method for the activity of f-CaO in fly ash or cement. The method establishes a reference conductivity using a specifically screened f-CaO standard sample, and quantitatively characterizes the hydration reaction activity of f-CaO by the ratio of the actual conductivity to the reference conductivity. The detection is completed within 30 minutes.

[0057] Hydration reactivity refers to the ease with which f-CaO reacts with water to form Ca(OH)2 in the cement hydration environment. Higher activity indicates that the reaction is easier to occur and the risk of delayed hydration is lower. Hydration reactivity is represented by the activity index L. The higher the L, the higher the ionization activity of f-CaO in the ethylene glycol extraction system, reflecting that it tends to complete the reaction in the early stage of cement hydration, thereby reducing the risk of delayed expansion after hardening. The lower the activity index L, the denser the f-CaO or the more severe the surface coating, the higher the risk of delayed hydration and the greater the probability of poor stability.

[0058] In one example, a rapid quantitative detection method for f-CaO activity in fly ash or cement includes the following steps:

[0059] (1) Select f-CaO standard samples based on the activity of f-CaO.

[0060] In a specific example, the following steps are included:

[0061] Several equal masses of analytical grade calcium carbonate were calcined to constant weight at temperatures of 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, and 1350℃, respectively, to obtain the corresponding first calcined products.

[0062] The f-CaO content in the first calcined product was determined by the f-CaO method in the "Chemical Analysis Methods for Cement" (GB / T 176-2017). When the difference between the measured value and the weighed value did not exceed ±5% of the weighed value, f-CaO was considered to have been obtained and used for the next step.

[0063] The first calcined product identified as f-CaO was mixed into fly ash or cement without f-CaO, homogenized, and then subjected to stability testing to obtain calcined products whose stability met the specifications. The sample with the lowest corresponding calcination temperature was selected from the first calcined products that met the stability requirements as the f-CaO standard sample.

[0064] In the optional example, the stability test is conducted in accordance with the "Standard Consistency Water Requirement, Setting Time and Soundness Test Method for Cement" (GB / T 1346-2011).

[0065] For example, analytical grade calcium carbonate was calcined at 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, and 1350℃ respectively. After stability testing, the Reichelckel expansion value of the product calcined at 950℃ after being mixed with fly ash was 1.0 mm (meeting the requirement of ≤5.0 mm), which was the lowest value among all the temperature that met the requirements. Therefore, it was determined to be the preparation temperature of f-CaO standard sample.

[0066] It should be noted that the preparation temperature is based on the experimental conditions (specific raw materials, equipment, and heating rate). In practical applications, the minimum temperature can be re-selected according to specific conditions.

[0067] (2) Add different contents of f-CaO standard samples to several equal masses of fly ash or cement to obtain a series of standard samples; wherein the fly ash does not contain f-CaO.

[0068] Understandably, the number of standard samples should be at least 5. To improve accuracy, the number of standard samples can be increased. The content of f-CaO can be progressively increased in a regular manner. For example, the content of f-CaO can range from 0.5 wt.% to 10 wt.%, with a value set every 0.5%. Alternatively, it can be progressively increased in a non-regular manner.

[0069] (3) Measure the conductivity of f-CaO in each standard sample and establish the relationship between f-CaO content and reference conductivity.

[0070] The conductivity of f-CaO in each standard sample can be determined directly according to the method in the Shanghai Municipal Engineering Construction Standard "Technical Specification for Application of Fly Ash Concrete" (DG / TJ08-230-2006).

[0071] In a specific example, determining the conductivity of f-CaO in each standard sample includes the following steps:

[0072] Each standard sample was added to a mixed solution of ethylene glycol and anhydrous ethanol, shaken thoroughly, and allowed to stand at room temperature until f-CaO was completely extracted to obtain an f-CaO solution. Then, the conductivity of each f-CaO solution was measured.

[0073] In some embodiments, the standing time at room temperature can be dynamically adjusted according to the mass fraction of f-CaO:

[0074] When the mass fraction of f-CaO is not greater than 5.0%, let it stand at room temperature for 10 minutes;

[0075] When the mass fraction of f-CaO is greater than 5.0% and not greater than 8.0%, let it stand at room temperature for 20 minutes;

[0076] When the mass fraction of f-CaO is greater than 8.0%, let it stand at room temperature for 30 minutes.

[0077] (4) Determine the content P of f-CaO in the test sample of equal mass to the standard sample, and obtain the reference conductivity σ0 corresponding to P based on the relationship between the f-CaO content and the theoretical active conductivity.

[0078] In an optional example, the content P of f-CaO in the fly ash to be tested, which is of equal mass to the standard sample, is determined according to the national standard "Cement Chemical Analysis Methods" (GB / T 176-2017).

[0079] The actual conductivity σ of f-CaO in a sample of equal mass to the standard was determined. ’ ; Determine σ ’ The procedure can be carried out directly according to the method in the Shanghai Municipal Engineering Construction Standard "Technical Specification for Application of Fly Ash Concrete" (DG / TJ08-230-2006).

[0080] In a specific example, σ is measured. ’ Includes the following steps:

[0081] The sample to be tested was added to a mixed solution of ethylene glycol and anhydrous ethanol (volume ratio 2:1), shaken thoroughly, and allowed to stand at room temperature until f-CaO was completely extracted. The conductivity of the solution was then measured to obtain σ. ’ .

[0082] (5) Based on the reference conductivity σ0 and the actual conductivity σ ’ The activity index L of f-CaO in the sample to be tested was obtained.

[0083] In an optional example, based on the reference conductivity σ0 and the actual conductivity σ ’ The activity index L of f-CaO in the sample to be tested is obtained and calculated according to formula (1):

[0084] (1)

[0085] In the formula, L is the activity index; σ' is the actual conductivity in μs / cm; and σ0 is the reference conductivity in μs / cm.

[0086] (6) Determine the activity level of f-CaO in the sample based on the calculated activity index L:

[0087] When L=100%, the activity of f-CaO in the test sample is determined to be equivalent to that of the f-CaO standard sample.

[0088] When L < 100%, it is determined that the activity of f-CaO in the test sample is lower than that of the f-CaO standard sample, and that f-CaO in the test fly ash has a dense surface coating or lattice defects.

[0089] The entire testing process was completed within 30 minutes.

[0090] In some embodiments, the conductivity measurement process includes: taking two consecutive measurements using a calibrated conductivity meter, and using the average of the two measurements as the conductivity value; wherein the relative error of the two parallel tests is not greater than 10%, and if the relative error is greater than 10%, the measurement is repeated.

[0091] It should be noted that the 'activity' mentioned in this invention does not refer to the direct hydration reaction rate of f-CaO in the cement hydration system, but rather to the ionization activity of f-CaO in the ethylene glycol-anhydrous ethanol extraction system. The principle is that the lattice integrity and surface density of f-CaO directly affect the penetration rate of ethylene glycol molecules and the release rate of Ca²⁺, manifested as differences in conductivity. Furthermore, lattice integrity and surface density determine the degree of hydration delay of f-CaO in cement paste—the more complete the lattice and the denser the surface, the more difficult it is for ethylene glycol to penetrate (lower conductivity), and the more difficult it is for early reactions in cement hydration (higher risk of delayed expansion). Therefore, this invention indirectly and quantitatively characterizes the potential reactivity of f-CaO through ethylene glycol extraction conductivity, thereby predicting its impact on fly ash stability.

[0092] Rapid test method for volume stability of fly ash or cement

[0093] Based on the aforementioned rapid quantitative detection method for f-CaO activity in fly ash or cement, this invention provides an exemplary rapid testing method for the volume stability of fly ash or cement. This method utilizes the aforementioned method to determine the f-CaO activity index L and actual mass fraction P in the sample, and combines this with a pre-established fly ash or cement stability contour map to predict the Reichstag expansion value. The stability determination is completed within 30 minutes, and includes the following steps:

[0094] Industrial limestone is calcined until constant weight to obtain a second calcined product; in a preferred example, industrial limestone is calcined at 1350°C until constant weight to obtain a second calcined product.

[0095] Different amounts of the second calcination product were added to several equal masses of fly ash or cement to obtain a series of fly ash or cement samples; wherein the fly ash or cement did not contain f-CaO.

[0096] Understandably, the second calcined product is different from the first calcined product because it uses analytical grade calcium carbonate as raw material. The first calcined product is pure f-CaO (i.e., f-CaO standard sample), while the second calcined product uses industrial limestone as raw material and contains impurities. Therefore, the corresponding standard sample and sample are not the same substance.

[0097] The f-CaO content and f-CaO activity index of each fly ash or cement sample were determined according to the aforementioned method, as well as the Reichstag expansion value of each fly ash or cement sample.

[0098] Subsequently, based on the f-CaO content, f-CaO activity index, and Reichstag expansion value, contour maps of fly ash or cement stability were obtained.

[0099] The f-CaO content and the f-CaO activity index in the test sample were determined according to the aforementioned method, using a sample of equal mass to that of fly ash or cement. Then, the corresponding Le Chatelier expansion value was obtained based on the aforementioned fly ash or cement stability contour map. The Le Chatelier expansion value was used to determine whether the test sample met the stability requirements.

[0100] In an optional example, the stability requirement of the test sample is determined based on the obtained expansion value of the Le Chatelier clip. The determination criterion is: when the expansion value of the Le Chatelier clip is ≤5.0 mm, the test sample meets the stability requirement.

[0101] Understandably, the stability contour maps of fly ash or cement can be obtained by fitting the corresponding f-CaO content, f-CaO activity index, and Le Chatelier expansion value, and then drawn according to common plotting methods in this field; and

[0102] The Reichelckel expansion value was obtained by conducting a stability test in accordance with the "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" (GB / T 1346-2011).

[0103] In some embodiments, the process of drawing a contour map of fly ash or cement stability includes: using no less than 20 sets of measured data as sample data sources to perform PPR modeling and fitting, and drawing contour maps based on the modeling results, for example, using Origin software; wherein, the expansion value interval between adjacent contour lines in the contour map is 0.5 mm.

[0104] It is understandable that if the sample to be tested is fly ash, then the corresponding matrix throughout the process is fly ash; if the sample to be tested is cement, then the corresponding matrix throughout the process is cement.

[0105] The fly ash or cement without f-CaO used in this invention refers to fly ash or cement with f-CaO of 0 as detected by XRF.

[0106] The Le Chatelier clip in this invention is the Le Chatelier clip expansion value.

[0107] This invention establishes the f-CaO activity index L as a quantitative evaluation parameter for activity, and establishes a volume stability evaluation system with the actual mass fraction P of f-CaO and the activity index L as two-dimensional evaluation parameters and the Le Chatelier expansion value as the evaluation target. This enables rapid evaluation of the volume stability of fly ash or cement, which can meet the requirements for rapid acceptance of projects.

[0108] To facilitate better understanding, the present invention will be further described below with reference to specific examples, but the preparation process is not limited to this, and the content of the present invention is not limited to this.

[0109] Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0110] Example 1

[0111] [Select f-CaO standard sample]

[0112] (1) Place an appropriate amount of CaCO3 (analytical grade) into a porcelain crucible that has been ignited and cooled, place it in a muffle furnace and ignite it at temperatures of 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, and 1350℃ until constant weight, and then place it in a desiccator to cool to room temperature.

[0113] (2) Weigh 0.5g of the sample calcined at different temperatures using a balance of 0.01g. Determine the f-CaO content in the sample by referring to the f-CaO method in Cement Chemical Analysis Method (GB / T 176-2017). If the difference between the measured value and the weighed value does not exceed ±5% of the weighed value, the sample is identified as f-CaO.

[0114] (3) The f-CaO samples calcined at different temperatures were mixed with fly ash containing nearly 0% f-CaO at a mass fraction of 4% and fully homogenized. The stability test was carried out in accordance with the "Standard Consistency Water Requirement, Setting Time and Soundness Test Method for Cement" (GB / T 1346-2011). The f-CaO that meets the standard requirements is identified as high-activity f-CaO. The high-activity f-CaO with the lowest calcination temperature was selected as the f-CaO standard sample. That is, in this test, f-CaO calcined to constant weight at 950℃ was selected as the f-CaO standard sample.

[0115] Example 2

[0116] [Establish the relationship between f-CaO content and baseline conductivity]

[0117] (1) Add different masses of f-CaO standard samples to 20 fly ash (excluding f-CaO) to obtain fly ash standard samples with different f-CaO contents. The theoretical combination is shown in Table 1.

[0118] Table 1

[0119] 1 0.5000 0.50 0.0025 2 0.5000 1.00 0.0050 3 0.5000 1.50 0.0075 4 0.5000 2.00 0.0100 5 0.5000 2.50 0.0125 6 0.5000 3.00 0.0150 7 0.5000 3.50 0.0175 8 0.5000 4.00 0.0200 9 0.5000 4.50 0.0225 10 0.5000 5.00 0.0250 11 0.5000 5.50 0.0275 12 0.5000 6.00 0.0300 13 0.5000 6.50 0.0325 14 0.5000 7.00 0.0350 15 0.5000 7.50 0.0375 16 0.5000 8.00 0.0400 17 0.5000 8.50 0.0425 18 0.5000 9.00 0.0450 19 0.5000 9.50 0.0475 20 0.5000 10.00 0.0500

[0120] (2) According to Table 1, weigh 20 fly ash standard samples with a concentration of 0.01% and place them in a 60mL Erlenmeyer flask. Prepare an ethylene glycol-anhydrous ethanol solution at a ratio of 2:1 of ethylene glycol (analytical grade) and anhydrous ethanol (analytical grade). Measure 30mL of the ethylene glycol-anhydrous ethanol solution and pour it into the 60mL Erlenmeyer flask containing the fly ash standard samples. Shake thoroughly and let stand at room temperature for 10-30 min (determine the specific time based on the f-CaO content to ensure complete extraction). Then, use a calibrated conductivity meter to measure the corresponding conductivity as the reference data, as shown in Table 2. Obtain the relationship between f-CaO content and reference conductivity. Results Figure 1 As shown, the relationship between the baseline conductivity (y) and the f-CaO content (P) can be obtained by fitting as y = 12.1713*x + 8.075.

[0121] Table 2

[0122] 1 0.5005 0.56 0.0028 13.37 10 2 0.5001 1.00 0.0050 16.37 10 3 0.5007 1.52 0.0076 25.56 10 4 0.5004 2.18 0.0109 33.33 10 5 0.5000 2.68 0.0134 41.92 10 6 0.5001 3.02 0.0151 45.38 10 7 0.5001 3.48 0.0174 51.42 10 8 0.5005 3.96 0.0198 60.24 10 9 0.5002 4.48 0.0224 65.22 20 10 0.5004 5.02 0.0251 71.18 20 11 0.5014 5.52 0.0276 74.07 20 12 0.5010 5.98 0.0299 80.17 20 13 0.5015 6.42 0.0321 89.07 20 14 0.5010 7.02 0.0351 95.27 20 15 0.5008 7.54 0.0377 100.70 20 16 0.5010 8.04 0.0402 104.20 20 17 0.5000 8.54 0.0427 110.90 30 18 0.5007 9.06 0.0453 115.70 30 19 0.5008 9.50 0.0475 120.20 30 20 0.5007 9.98 0.0499 131.30 30

[0123] Note 1. Based on the actual situation, manually weigh the mass of the f-CaO standard sample to get as close as possible to the theoretical value, and then convert it into the corresponding percentage;

[0124] 2. The extraction time should be appropriately increased according to the increase of f-CaO content, which is conducive to the full extraction of f-CaO;

[0125] 3. The conductivity result is measured twice within a short period of time, and the average value of the two measurements is taken as the conductivity value;

[0126] 4. The error of parallel tests should be limited to within 10%; if it exceeds 10%, the test should be repeated.

[0127] Example 3

[0128] [f-CaO Activity Test in Fly Ash]

[0129] (1) The content of f-CaO in 0.5000 g of fly ash was determined according to the national standard "Cement Chemical Analysis Methods" (GB / T 176-2017).

[0130] (2) Based on the relationship between the content of f-CaO and the reference conductivity obtained in Example 2, calculate the reference conductivity σ0 corresponding to the content of f-CaO P.

[0131] (3) Weigh 0.5000g of the fly ash to be tested, and test the actual conductivity σ of f-CaO in the fly ash to be tested according to the steps of f-CaO conductivity calibration in Example 2. ’ .

[0132] (4) The activity index L of f-CaO in the fly ash to be tested is calculated according to formula (1).

[0133] Example 4

[0134] [Relationship between f-CaO content, f-CaO activity, and volume stability in fly ash]

[0135] Industrial limestone was calcined at 1350℃ for 1 hour, and different masses of calcined products were added to 20 fly ash samples (excluding f-CaO) to obtain fly ash samples. The theoretical ratio is shown in Table 3. The f-CaO content (determined according to the method in Example 3), f-CaO activity index (determined according to the method in Example 3), and the Reichstag snap-fit ​​value of the fly ash samples were tested (referring to the "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" (GB / T 1346-2011)). The results are shown in Table 3.

[0136] Table 3

[0137] 1 0.5001 0.0038 0.62 0.0031 9.03 15.62 57.81 1.0 2 0.5019 0.0064 1.06 0.0053 10.28 20.93 49.12 1.5 3 0.5005 0.0097 1.60 0.0080 17.17 27.53 62.37 2.0 4 0.5010 0.0123 2.02 0.0101 22.00 32.61 67.46 2.1 5 0.5006 0.0158 2.60 0.0130 27.44 39.68 69.15 2.3 6 0.5011 0.0182 2.99 0.0150 31.04 44.51 69.74 2.5 7 0.5002 0.0210 3.46 0.0173 34.57 50.17 68.90 3.5 8 0.5005 0.0243 4.00 0.0200 41.18 56.71 72.61 4.2 9 0.5007 0.0269 4.41 0.0221 45.92 61.80 74.31 5.3 10 0.5006 0.0303 4.97 0.0249 52.39 68.62 76.35 5.5 11 0.5007 0.0334 5.49 0.0275 51.55 74.92 68.80 6.1 12 0.5006 0.0367 6.03 0.0302 58.13 81.50 71.32 6.2 13 0.5001 0.0386 6.36 0.0318 65.80 85.47 76.99 6.5 14 0.5009 0.0425 6.99 0.0350 69.45 93.12 74.58 7.2 15 0.5005 0.0454 7.47 0.0374 74.53 99.03 75.26 9.3 16 0.5012 0.0487 8.00 0.0401 73.15 105.46 69.37 11.4 17 0.5009 0.0516 8.48 0.0425 80.18 111.35 72.01 14.5 18 0.5010 0.0548 9.00 0.0451 83.78 117.64 71.22 18.8 19 0.5001 0.0577 9.50 0.0475 88.15 123.68 71.27 21.3 20 0.5013 0.0614 10.07 0.0505 94.48 130.69 72.30 25.6

[0138] Based on f-CaO content, f-CaO activity index, and stability T-Rayet clip value, using the above 20 sets of data, PPR modeling was employed to fill in the gaps in the tested data. The PPR model was then used to fit and supplement the detailed dataset. Using Origin software, f-CaO content was set as variable X, f-CaO activity index as variable Y, and stability value as variable Z. Contour plots were then drawn, and the results are shown below. Figure 2 As shown.

[0139] The content of f-CaO in 0.5000g of fly ash to be tested and the activity index of f-CaO in fly ash to be tested were determined. Then, the corresponding Reichelckel expansion value was obtained according to the fly ash stability contour map. When the Reichelckel expansion value is ≤5.0 mm, the fly ash to be tested meets the stability requirements.

[0140] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.

Claims

1. A rapid quantitative detection method for f-CaO activity in fly ash or cement, characterized in that, Includes the following steps: S1-1. Prepare highly active f-CaO standard samples and establish an activity benchmark. Analytical pure calcium carbonate was calcined to constant weight at multiple gradient temperature points in the range of 950℃ to 1350℃ to obtain a series of calcined products. The f-CaO content in each calcined product was determined, and calcined products in which the difference between the measured value and the theoretical weighing value was within ±5% of the theoretical weighing value were identified as candidate f-CaO samples. Each candidate f-CaO sample was incorporated into fly ash or cement matrix without f-CaO at the same mass fraction and homogenized, and then subjected to Le Chatelier stability test. Among the candidate samples with a Rabcat expansion value of no more than 5.0 mm, the sample with the lowest corresponding calcination temperature was selected as the f-CaO standard sample, and the activity index was defined as 100% as the benchmark. S1-2. Establish a quantitative relationship between f-CaO content and reference conductivity. Different mass fractions of the f-CaO standard samples were added to several equal masses of fly ash or cement matrix containing no f-CaO to obtain a series of standard samples with an f-CaO mass fraction of 0.5% to 10.0%. Each standard sample was added to a mixed solution of ethylene glycol and anhydrous ethanol in a volume ratio of 2:1, and extracted by standing at room temperature for 10 min to 30 min until the f-CaO extraction reached a stable state. The conductivity of each extract was measured, and a quantitative relationship curve between f-CaO content and reference conductivity was established. S1-3. Determine the actual conductivity of the sample to be tested. Weigh the sample to be tested with the same mass as the standard sample, add it to a mixed solution of ethylene glycol and anhydrous ethanol in a volume ratio of 2:1, and extract it by standing for 10 min to 30 min under the same room temperature conditions until the f-CaO extraction reaches a stable state. Measure the actual conductivity σ' of the extract. S1-4, Calculate the activity index The actual mass fraction P of f-CaO in the sample to be tested is determined, and the reference conductivity σ0 corresponding to the actual mass fraction P is obtained according to the quantitative relationship curve described in step S1-2; the activity index L of f-CaO in the sample to be tested is calculated according to formula (1): (1) In the formula: L is the activity index; σ' is the actual conductivity, in μs / cm; σ0 is the reference conductivity, in μs / cm; S1-5. Determine the f-CaO activity in the sample to be tested. The activity level of f-CaO in the sample to be tested is determined based on the activity index L calculated in steps S1-4. When L=100%, the activity of f-CaO in the test sample is determined to be equivalent to that of the f-CaO standard sample. When L < 100%, the activity of f-CaO in the test sample is determined to be lower than that of the f-CaO standard sample; When L > 100%, the activity of f-CaO in the test sample is determined to be higher than that of the f-CaO standard sample; The entire testing process was completed within 30 minutes.

2. The rapid quantitative detection method for f-CaO activity in fly ash or cement according to claim 1, characterized in that, The gradient temperature in step S1-1 is a temperature point with an interval of 50℃, including: 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃ and 1350℃.

3. The rapid quantitative detection method for f-CaO activity in fly ash or cement according to claim 1, characterized in that, The conductivity measurement process in steps S1-2 and S1-3 both include: taking two consecutive measurements using a calibrated conductivity meter, and using the average of the two measurements as the conductivity value; wherein the relative error of the two parallel tests is not greater than 10%, and if the relative error is greater than 10%, the measurement is repeated.

4. A rapid test method for the volume stability of fly ash or cement, characterized in that, The method described in any one of claims 1 to 3 is used to determine the activity index L and actual mass fraction P of f-CaO in the sample to be tested, and the Reichstag expansion value is predicted by combining it with a pre-established fly ash or cement stability contour map, and the stability determination is completed within 30 minutes; including the following steps: S2-1. Preparation of industrial f-CaO samples Industrial limestone was calcined at 1350℃ to constant weight to obtain industrial f-CaO samples; S2-2. Prepare a series of fly ash or cement samples and determine their soundness parameters. Different mass fractions of the industrial f-CaO sample were added to several equal masses of fly ash or cement matrix that did not contain f-CaO to obtain a series of fly ash or cement samples. The actual mass fraction and activity index of f-CaO in each fly ash or cement sample are determined by the method described in any one of claims 1 to 3, and the Reichelckel expansion value of each fly ash or cement sample is determined by performing the Reichelckel expansion test. S2-3. Establish contour maps of fly ash or cement stability. Using the actual mass fraction of f-CaO as variable X, the activity index of f-CaO as variable Y, and the expansion value of the Le Chatelier as variable Z, the data were fitted using the projection pursuit regression (PPR) model, and contour maps of the stability of fly ash or cement were drawn. S2-4. Rapidly determine the stability of the sample to be tested. The actual mass fraction P and activity index L of f-CaO in the sample to be tested are determined, and the predicted values ​​of the Le Chatelier expansion corresponding to P and L are retrieved from the stability contour map of fly ash or cement. When the predicted expansion value of the Le Chatelier clip is not greater than 5.0 mm, the volume stability of the sample to be tested is deemed to be qualified.

5. The rapid test method for the volume stability of fly ash or cement according to claim 4, characterized in that, The process of drawing the fly ash or cement stability contour map in step S2-3 includes: using no less than 20 sets of measured data as sample data sources to perform the PPR modeling and fitting, and drawing contour maps based on the modeling results, wherein the expansion value interval between adjacent contour lines in the contour map is 0.5 mm.

6. The rapid test method for the volume stability of fly ash or cement according to claim 4, characterized in that, The process of retrieving the predicted values ​​of the Le Chatelier expansion corresponding to P and L from the stability contour map of fly ash or cement includes: obtaining the predicted values ​​of the Le Chatelier expansion corresponding to P and L through linear interpolation or model calculation based on the stability contour map of fly ash or cement.

Citation Information

Patent Citations

  • Device for rapidly detecting free calcium oxide in fly ash

    CN221803886U